Učili smo se raziskovati - Huzjan, Vanja (Glasnik Slovenskega etnološkega društva, 1993)
The purpose of the paper is to present the work of ethnologists at the International research camp in Obrov that lasted from 10th to 22nd of August 1992. The central part of the report presents different levels of a basis of the qualitative research. The survey also presents levels of a documentation wich we dealt with to authenticate the Saint's day wich is held every year on the 16th of August in Obrov. The autor ends her report by presenting her own experiences of the interaction between an informer and a researcher and she also enumerates some methodical problems that appeared during the work at the camp.
Keywords: ethnology; etnologija; Obrov; raziskovalne delavnice; research workshops; Slovenia